DEVELOPING EMOTIONAL INTELLIGENCE IN PRESCHOOL CHILDREN THROUGH PLAY-BASED ACTIVITIES (International journal of artificial intelligence, 2026)
Emotional intelligence (EI) is a critical component of early childhood development, encompassing the ability to recognize, understand, express, and regulate emotions while fostering empathy and positive social interactions. This article explores the role of play-based activities in developing EI among preschool children aged 3-6 years. Drawing on international and Uzbek research, it examines theoretical foundations, effective play interventions such as role-playing, cooperative games, and emotion-focused dramatization, and their measurable impacts on emotional awareness, self-regulation, and social competence. A hypothetical mixed-methods study illustrates practical implementation, showing significant improvements in emotional skills through structured yet child-led play. The findings underscore that play-based approaches provide developmentally appropriate, engaging contexts for EI growth, with implications for educators, parents, and policymakers. Integrating such activities into preschool curricula can yield long-term benefits for academic success, mental health, and social adaptation.